Loss and gain of land of Manpura island of Bhola district: An integrated approach using remote sensing and GIS - Ali, Md Shahjahan; Haque, Md Fazlul; Rahman, Shah Md Mizanur; Iqubal, Kazi Farhed; Nazma, Ms; Ahmed, Ashfaque (Dhaka University Journal of Biological Sciences, 2013)
The erosion-accretion pattern in Manpura island has been depicted over a 37 years period from 1973 - 2010. Data of different years revealed that the island is under the threat of erosion and the total area has gradually decreased from 148 to 114 Km2. Although Manpura island is under the threat of erosion, some lower mid parts get in irregular erosion - accretion processes, where area of water bodies has decreased up to a significant level (15 Km2) and the area of mangrove forests have also decreased to 6 Km2. According to this study, total land loss of Manpura island is 34 Km2 in the last 37 years and major erosion took place along the northern shore line. Dhaka Univ. J. Biol. Sci. 22(1): 29-37, 2013 (January)